Assessing the importance of stakeholder analysis in utilizing homegarden (pekarangan) agrotourism in East Java, Indonesia - Trisnanto, Atang; Soekmadi, Rinekso; Arifin, Hadi Susilo; Noorachmat, Bambang Pramudya (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The management of homegarden (pekarangan) agrotourism in Banyuwangi involves stakeholders from various part. However, existing stakeholders are still not properly managed, and there are no rules that regulate the interaction and role of each stakeholder. This study aimed to map and analyze the stakeholders involved in the homegarden-based agrotourism program in the Banyuwangi Regency. Some of the methods used in this study are stakeholder identification, stakeholder classification, and the relationship between stakeholders. The results showed that the stakeholders involved consisted of three groups: local government groups (tourism offices, agricultural offices, and village governments), community groups (pokdarwis, farmer groups, and communities), and private groups (associations of tourism actors and tourism/private business actors). The stakeholders included in quadrant 1 (key players) are the Tourism Office, Agriculture Office, Village Tourism Awareness Group (Kelompok Sadar Wisata/Pokdarwis), and Village Government. Quadrant 2 (subject) consisted of farmer groups and communities located around the tourist area. Quadrant 3 (Context Setter) consisted of an association between tourist actors and business/private owners, and Quadrant 4 (Crowd) consisted of universities and Regional Development Planning Board (Badan Perencanaan Pembangunan Daerah/Bappeda). The relationship between stakeholder groups involved in the development of homegarden agrotourism in Banyuwangi can be seen through operational activities in the field and official documents that regulate this relationship. Relationships between stakeholders are grouped into three groups: communication, coordination, and cooperation.